Devulcanization of natural rubber vulcanizates by Bacillus cereus TISTR 2651 - B. Kaewpetch; S. Prasongsuk; S. Poompradub (eXPRESS Polymer Letters)
The ability of Bacillus cereus TISTR 2651 to perform biological devulcanization of natural rubber cured by conventional vulcanization (CV), semi-efficient vulcanization or efficient vulcanization was studied. Among the three curing systems, B. cereus TISTR 2651 could specifically devulcanize rubber products formed from the CV system the best, removing 26.44% of the sulfur within 20 days. Moreover, B. cereus TISTR 2651 could oxidize and desulfurize the sulfide crosslinks in the CV rubber and transform them to oxygen-containing sulfur-based groups via the 4S pathway. Additionally, the molecular weight, crosslink density and gel fraction of the CV rubber were also significantly decreased from the original levels. Horikx analysis was used to propose the mechanism of bacterial devulcanization. Finally, ground tire rubber (GTR) was devulcanized by B. cereus TISTR 2651 and the percentage of sulfur removal was about 27.98 for 20 days, where similar results were also obtained. Accordingly, B. cereus TISTR 2651 can be applied for the management of rubber waste, leading towards a solution of this environmental problem.